Comparison of Treadmill Gait Between a Pediatric-Aged Individual With SYNGAP1-Related Intellectual Disability and a Fraternal Twin - Layne, Charles S.; Malaya, Christopher A.; Young, David R.; Suter, Berhard; Holder, Jimmy L. (Frontiers in Human Neuroscience, 2022)
SYNGAP1-related Intellectual Disability (SYNGAP1-ID) is a rare neurodevelopmental condition characterized by profound intellectual disability, gross motor delays, and behavioral issues. Ataxia and gait difficulties are often observed but have not yet been characterized by laboratory-based kinematic analyses. This investigation identified gait characteristics of an individual with SYNGAP1-ID and compared these with a neurotypical fraternal twin. Lower limb kinematics were collected with a 12-camera motion capture system while both participants walked on a motorized treadmill. Kinematic data were separated into strides, and stride times calculated. Sagittal plane hip, knee, and ankle joints were filtered and temporally normalized to 100 samples. Minimum and maximum joint angles, range of motion (ROM) and angular velocities were obtained for each joint by stride and averaged for each participant. ROM symmetry between left and right joints was also calculated. Discrete relative phase (DRP) was used to assess coordination and variability between joints within a single limb and compared across limbs. Phase portraits were calculated by joint, and their areas were computed with a MATLAB script. Statistical parametric mapping (SPM) was used to assess differences in joint angle waveforms between participants. P1, the individual with SYNGAP1-ID, displayed significantly reduced stride times relative to the fraternal twin, i.e., P2. A majority of minimum, maximum angles, ROMs, and angular velocities were significantly different between P1 and P2. Phase portrait areas were consistently less in P1 relative to P2 and there were differences in knee and ankle symmetries. DRP showed no differences between individuals, suggesting that P1’s coordinative events remained similar to those observed during neurotypical gait (P2). SPM revealed significant differences between the left and right legs at the knee and ankle joints of P1 while P2 joint left and right waveforms were nearly identical for all joints. Additionally, SPM revealed there were significant differences between P1 and P2 for all joints. This investigation identified several major gait features of an individual with SYNGAP1-ID and provided a comprehensive characterization of these features by utilizing both linear and non-linear analyses. While limited in generalizability, this report provides a strong quantitative appraisal of gait in an individual with SYNGAP1-ID as well as an analysis pathway for future investigations.